Students' Perceptions towards Biology Learning based on the Implementation of the Emancipated Curriculum - Kaharudin, La Ode; Ridzal, Dewi Asriani; Ismawati, Nur (IAIN Kendari, 2024)
This study aims to interpret students' perception in a public school of SMA Negeri 4 Baubau about biology learning activities based on Implementasi Kurikulum Merdeka (IKM) or the Implementation of the Emancipated Curriculum. The research is a qualitative study with a sample of 70 grade X students of SMA Negeri 4 Baubau. The study employed questionnaires based on indicators of students' perceptions and administered interviews to strengthen the data findings. Data analysis techniques are qualitative data analysis which includes collecting data, reducing data, presenting data, and concluding the findings, then testing the validity of the data (i.e. using source triangulation, technique triangulation, and time triangulation). The results show that the indicator of student participation in biology learning obtained a percentage of 75.61%, falling into the very good category. Similarly, other indicators, including effective biology learning (78.02%) and equal access towards biology learning (77.32%) also fall into the very good category. It, therefore, can be concluded that IKM-based biology learning activities at SMA Negeri 4 Baubau are very well received by students. However, improvements in learning tools and differentiated instructions are needed to optimize the experience for all students.